2013
DOI: 10.1016/j.fra.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential and amino acid analysis of underutilized tropical fruit Limonia acidissima L.

Abstract: Objective: Limonia acidissima L. an underutilized edible fruit was evaluated for its antioxidant activity, free radical scavenging ability, proximate and amino acid analysis using established in vitro assay models. Methods: 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, trolox equivalent antioxidant capacity (TEAC) assay, hydroxyl radical scavenging activity (HRSA), ferric reducing antioxidant power (FRAP) assay, nitric oxide radical (NO) scavenging activity, total antioxidant activity (TAA) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 52 publications
4
30
0
1
Order By: Relevance
“…The bioactive compounds present in Limonia acidissima Fruit acts as antioxidants in a number of ways. The phenolics compounds are attributed by their hydroxyl groups in the termination reaction to rupture the cycle of generation of new radicals 68 , while the polyphenol and flavanoids have therapeutic uses due to their stronger antioxidant properties 34 . Respiratory burst involves the synthesis of intracellular superoxide anion that is quantified by nitroblue tetrazolium (NBT) assay 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioactive compounds present in Limonia acidissima Fruit acts as antioxidants in a number of ways. The phenolics compounds are attributed by their hydroxyl groups in the termination reaction to rupture the cycle of generation of new radicals 68 , while the polyphenol and flavanoids have therapeutic uses due to their stronger antioxidant properties 34 . Respiratory burst involves the synthesis of intracellular superoxide anion that is quantified by nitroblue tetrazolium (NBT) assay 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The fruit has high nutritive value and contains important phyto constituents such as flavonoid, phytosterols, glycosides, saponins, tannins, coumarins, triterpenoids, carbohydrates, vitamins and amino acids [30][31][32][33] . Recent studies show that the fruit consist of essential amino acids, wound healing and has rich antioxidant properties 34 . Our earlier studies reported that supplementing L. acidissima in fish diets stimulated the growth performance of fresh water carps Cyprinus carpio and Cirrhinus mrigala 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Lấy mẫu đem đi trích li bằng methanol 70% (1:10) ủ hai giờ để trong bóng tối, sau đó pha loãng (1:10) cho vào ống nghiệm, thêm vào 0,5 ml thuốc thử Folin-Ciocalteu, lắc đều. Sau ba phút thêm vào 2 ml dung dịch Na 2 CO 3 20%, lắc đều, ủ trong nước sôi 100 o C trong một phút và làm lạnh nhanh, sau đó lắc đều và đo độ hấp thu ở bước sóng 450 nm [12].…”
Section: Phương Pháp Phân Tíchunclassified
“…The herbal plant Limonia acidissima is one of the important herbal drugs u n c o r r e c t e d p r o o f used in Ayurvedic systems of medicine [23] . It is also used against variety of conditions such as antimicrobial, hepatoprotective, antidiarrhoeal, anticancer, diuretic, hepatoprotective, antispermatogenic, antioxidant, anti diabetic and wound healing activities [24,25] .…”
Section: Introductionmentioning
confidence: 99%